Penerapan Model Pembelajaran PBL di Era Kurikulum Merdeka Belajar di SMA Kristen Tumou Tou Girian Bitung - Grace Miracle Lukas; Sukmarayu Pieter Gedoan; Wiesye MS Nangoy (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
In the learning process, teachers have not employed a variety of instructional models that align with the diverse learning styles of the students, resulting in a diminished interest in learning among the participants. Accordingly, it is anticipated that this study will enable teachers to engage students more effectively in the learning process, thereby cultivating a greater interest in learning. The objective of this research is to enhance the learning outcomes of students on the subject of Plant Growth and Development by implementing the Problem Based Learning (PBL) model at SMA Kristen Tumou Tou Girian Bitung. This study is a qualitative descriptive research. Data collection techniques include questionnaires, interviews, and document analysis. The research design employed is Classroom Action Research (CAR). The subjects of the study are 20 students from class XIA who experienced the implementation of the Problem Based Learning model. Data were gathered using both tests and observations. Classically, the students’ learning outcomes improved from 70% in cycle I to 100% in cycle II. Consequently, it can be concluded that the application of the Problem Based Learning method has enhanced the learning outcomes of the students in class XIA of the specialized program at SMA Kristen Tumou Tou Girian Bitung.